Advances of macroalgae biomass for the third generation of bioethanol production - Tan, I.S. (Chemical Industry Press, 2020)
In recent years, utilization of renewable sources for biofuel production is gaining popularity due to growing greenhouse gas (GHG) emissions which causes global warming. There has been a great effort in exploring alternative feedstock for bioethanol production. In this context, the production of third-generation bioethanol from macroalgae has emerged as an alternative feedstock to food crop-based starch and lignocellulosic biomass. This is mainly due to the fast growth rate of macroalgae, no competition with agricultural land, high carbohydrate content and relatively simple processing steps compared to lignocellulosic biomass. This review paper provides an insight of recent innovative approaches for macroalgae bioethanol production, including conventional and advanced hydrolysis process to produce fermentable sugar, various fermentation technologies, economic analysis and life cycle assessment. With the current technology maturity, efficient utilization of macroalgae as sustainable source for bioethanol and other value-added chemicals production could be achieved in the near future. Â© 2019 Elsevier B.V.